The Woman’s Womb as a Place of God’s Action and Creation - Chrostowski, Marcin (The Biblical Annals, 2023)
In the Hebrew Bible, the woman’s womb is rendered by three main nouns: רֶחֶם (most often translated as “womb”), בֶּטֶן (“belly”) and מֵעֶה (plural only: מֵעִים, “bowels”). Although these terms take on various shades of meaning, they very often refer to the female womb. In this context, they always appear in relation to God, who is particularly active in this field. This article aims to show the ways of God’s creative activity in the female womb, which also takes various metaphorical shades.